Gerakan renaissance: Relasi eropa dengan dunia islam - Wahid, Muhammad Aqil (Maliki Interdisciplinary Journal, 2025)
The relationship between the Western world and Islam is a very complex relationship and very complicated to deconstruct. This is inseparable from the natural phenomenon of cathexes between two different civilization structures. This type of research is descriptive qualitative. The method used is literature review. The data used is primary data, consisting of a collection of books, articles, and historical documents that discuss the Renaissance and Western colonialism in the Islamic world, and secondary data from articles and books that are relevant to the current study. Data were collected using reading and note-taking techniques. The data found were analyzed using Miles and Huberman's data analysis techniques, which include several stages: 1) Data reduction, 2) Data presentation, and 3) Drawing conclusions from the data found. Based on the research conducted, the researcher found a significant influence of Islamic culture on the Age of Enlightenment that occurred in Europe. This influence covers various fields of life, from science, culture, and social to medicine and also technology. In addition, Islamic civilization also has a great influence on the construction of human values, values of freedom, and also values of justice. Apart from that, the Islamic world, on the contrary, experienced a decline, plus it received strong pressure from European colonialism. Western nations came with three goals, namely greatness, luxury, and also the spread of religion. This was a fatal blow to the Islamic world, which was experiencing a crisis in various aspects of life.